Building Student Engagement Through Personalized Marketing: The Key to Student Loyalty in Educational Services - Rofiki, Moh.; Mahrosa, Safira (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the application of personalized marketing in education and its impact on emotional engagement and student loyalty. The study was conducted at Madrasah Aliyah Nurul Jadid, an Islamic boarding school-based institution that emphasizes personalized services, effective communication, and a relevant curriculum. The study used a qualitative case study approach, with teachers, students, and parents as subjects. Data were collected through in-depth interviews, participant observation, and documentation, and then analyzed thematically with triangulation to ensure validity. The results show that personalization, which tailors interactions, academic guidance, and extracurricular services to individual student characteristics, can create meaningful learning experiences, increase attention, foster feelings of appreciation, and strengthen emotional engagement. This approach also encourages students' social engagement in the school community and reduces the risk of disengagement. The findings emphasize the importance of integrating personalized interactions with Islamic boarding school culture to build stable, supportive, and sustainable educational relationships, as well as to strengthen the relationships among students, teachers, and the institution. This study contributes to the development of the concept of personalized marketing in the educational context, particularly in Islamic boarding schools, by highlighting the design, implementation, and significance of personalization strategies to increase student loyalty and retention.